Microwave-assisted hydrothermal carbonization for solid biofuel application: a brief review - Zulkornain, Muhammad Fikri; Shamsuddin, Abd Halim; Nomanbhay, Saifuddin; Md Saad, Juniza; Zhang, Ye Shui; Samsuri, Shafirah; Wan Ab Karim Ghani, Wan Azlina (Elsevier, 2021)
Carbon dioxide and greenhouse gas emissions have been a known threat globally. One of the significant contributors to this issue is coal usage in the power generation industry. Hydro-thermal carbonization (HTC) is considered one of the alternative methods for producing hydrochar to replace coal. Moreover, the application of microwave heating in HTC process is in demand due to its advantageous characteristics such as rapid heating and selective heating. This paper reviews microwave-assisted HTC (MAHTC) as an alternative solid biofuel with an emphasis on lignocellulosic biomass as the feedstock as it is abundant in nature, the influence of process parameters on the hydrochar quality and the kinetic models of hydrochar. Lastly, the challenges during scale-up design especially in terms of technical, economic and environment are discussed. This review would provide a comprehensive overview of MAHTC, which positioning a way forward for the energy and power sector.